C-terminal Domain of Chromogranin B Regulates Intracellular Calcium Signaling - Schmidt, Stefan (American Society for Biochemistry and Molecular Biology, 2011)
The versatility of intracellular calcium as a second messenger is seen in its ability to mediate opposing events such as neuronal cell growth and apoptosis. A leading hypothesis used to explain how calcium regulates such divergent signaling pathways is that molecules responsible for maintaining calcium homeostasis have multiple roles. For example, chromogranin B (CGB), a calcium binding protein found in secretory granules and in the lumen of the endoplasmic reticulum, buffers calcium and also binds to and amplifies the activity of the inositol 1,4,5-trisphosphate receptor (InsP(3)R). Previous studies have identified two conserved domains of CGB, an N-terminal domain (N-CGB) and a C-terminal domain (C-CGB). N-CGB binds to the third intraluminal loop of the InsP(3)R and inhibits binding of full-length CGB. This displacement of CGB decreases InsP(3)R-dependent calcium release and alters normal signaling patterns. In the present study, we further characterized the role of N-CGB and identified roles for C-CGB. The effect of N-CGB on calcium release depended upon endogenous levels of cellular CGB, whereas the regulatory effect of C-CGB was apparent regardless of endogenous levels of CGB. When either full-length CGB or C-CGB was expressed in cells, calcium transients were increased. Additionally, the calcium signal initiation site was altered upon C-CGB expression in neuronally differentiated PC12 and SHSY5Y cells. These results show that CGB has numerous regulatory roles and that CGB is a critical component in modulating InsP(3)R-dependent calcium signaling.